Prestige Restoration According to Afghan Legal System - Miakhil, Pasoon; Zadran, Amanullah (Integrated Journal for Research in Arts and Humanities, 2022)
Prestige Restoration is the means by which the convicted person returns to original state after being charged and convicted, and the convicted person acts to restore his or her dignity after serving imprisonment or punishment through legal and judicial channels. There several conditions for the restoration of prestige according to law, which are; to serve whole punishment, amnesty and mitigation of punishment, or suspension of punishment. In addition, two types of restoration of dignity are considered; restoration of dignity based on the law, and restoration of dignity according to the judiciary; Or Legal restoration dignity and judicial restoration of dignity.